TEKTONIK BATUAN PRA-TERSIER JAWA BARAT - -, Iyan Haryanto; -, Aldrin Ramadian; -, Faisal Helmi (Fakultas Teknik Geologi Universitas Padjadjaran, 2009)
The Pre-Tertiary Melange is the oldest rocks outcrop that found in Ciletuh area. Stratigraphically, this mélange is basement rock that overlaid unconformity by Tertiary sedimentary rocks, i.e. Ciletuh and Jampang FormationThe outcropping mechanism of Pre-Tertiary rock in this area due to up-tilting, thrusting and folding that followed by sliding. The product of sliding is represented by a elongate scarp toward the sea..